Early bilingualism influences early and subsequently later acquired languages in cortical regions representing control functions. (February 2014) - Wattendorf, Elise; Festman, Julia; Westermann, Birgit; Keil, Ursula; Zappatore, Daniela; Franceschini, Rita; Luedi, Georges; Radue, Ernst-Wilhelm; Münte, Thomas F.; Rager, Günter; Nitsch, Cordula
Early acquisition of a second language influences the development of language abilities and cognitive functions. In the present study, we used functional Magnetic Resonance Imaging (fMRI) to investigate the impact of early bilingualism on the organization of the cortical language network during sentence production. Two groups of adult multilinguals, proficient in three languages, were tested on a narrative task; early multilinguals acquired the second language before the age of three years, late multilinguals after the age of nine. All participants learned a third language after nine years of age. Comparison of the two groups revealed substantial differences in language-related brain activity for early as well as late acquired languages. Most importantly, early multilinguals preferentially activated a fronto-striatal network in the left hemisphere, whereas the left posterior superior temporal gyrus (pSTG) was activated to a lesser degree than in late multilinguals . The same brain regions were highlighted in previous studies when a non-target language had to be controlled. Hence the engagement of language control in adult early multilinguals appears to be influenced by the specific learning and acquisition conditions during early childhood. Remarkably, our results reveal that the functional control of early and subsequently later acquired languages is similarly affected, suggesting that language experience has a pervasive influence into adulthood. As such, our findings extend the current understanding of control functions in multilinguals.